PENGEMBANGAN MODUL PRAKTEK BERBASIS INQUIRY PADA MATA KULIAH MOTOR DIESEL DEPARTEMEN TEKNIK OTOMOTIF - Nurhidayat, Muslim; Rifdamon; Hasan Maksum; Iffarial Nanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Practical learning fundamentally requires support from a student-centered approach, one of which is through the application of inquiry-based learning. This model emphasizes stages of activity such as problem identification, question formulation, investigation, data processing, and drawing structured conclusions. However, in the implementation of practical work in the Diesel Engine course, the learning tools used still do not integrate a specific learning model. This results in students primarily following procedural work steps without actively engaging in the investigation process or developing critical thinking skills. Therefore, this research was conducted with the aim of developing a practical module based on the inquiry model to address the gap between the expected practical learning conditions and the reality encountered in the field. The method used in this study was Research and Development (R&D) with a Four-D (4D) development model limited to the development stage. The resulting product is an inquiry-based practical module structured following the stages of orientation, problem identification, hypothesis formulation, data collection, hypothesis testing, and conclusion drawing. Based on the validity test results, the developed practical module obtained an Aiken's V score of 0.958333333 for the material aspect, 0.955882353 for the inquiry construct aspect, 0.972222222 for the language aspect, and 0.902777778 for the practical module presentation aspect, all of which are considered valid. Therefore, the developed inquiry-based practical module is deemed suitable for use as a practical learning tool in the Diesel Engine course.